(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
This study examines the role of Self-Help Group (SHG)-led financial inclusion in promoting women’s economic empowerment in India, with special reference to Rajasthan. Based entirely on secondary data from National Bank for Agriculture and Rural Development, Ministry of Statistics and Programme Implementation, and International Institute for Population Sciences, the study adopts a descriptive and comparative analytical approach. The analysis focuses on institutional financial inclusion indicators such as SHG savings linkage, credit linkage, and bank-wise disbursement, alongside women’s economic participation indicators including bank account ownership, paid work, asset ownership, and decision-making participation. Findings indicate significant expansion in SHG-based institutional credit and strong growth in women’s formal financial participation. However, Rajasthan-level evidence shows that increased financial access has not fully translated into independent economic empowerment, as limitations persist in productive asset ownership, digital access, and income autonomy. The study concludes that while SHG-led financial inclusion has strengthened women’s institutional entry into formal finance, broader economic empowerment requires stronger support through livelihood generation, digital capability, and asset-building policies.